Clinical profile and outcome of dengue patients with atypical features in the pediatric age group in a tertiary care center of East India - Pal, Sumita; Roy, Basudha; Chattopadhyay, Amrit; Andra, Akhila; De, Gautam (Asian Journal of Medical Sciences, 2021)
Background: Dengue is one of the most widespread arthropod borne diseases worldwide with an annual incidence of 50–100 million cases per year. The recent resurgence of dengue in the pediatric population has created concern among pediatricians, especially due to increased incidence of atypical features, leading to delayed diagnosis and increased mortality. There are few studies regarding this due to under reporting of the cases. Aims and Objectives: This study aims to study the clinical profile and outcome of dengue patients between the age groups of 1 month and 12 years with special emphasis on patients with atypical features. Dengue patients with atypical presentation are easily misdiagnosed by physicians, especially in the pediatric age group which increases the morbidity and mortality. Materials and Methods: This was a retrospective observational study conducted from May 2018 to September 2019 in the Department of Pediatrics, CNMCH. All pediatric patients who were dengue IgM or dengue NS1 positive were included in the study and their course of stay was followed through hospital records. The data were statistically analyzed through SPSS 16.0 software. Results: Sixty-two dengue patients were included in the study. Thirty-two patients presented as mild febrile illness, classical dengue fever (DF), dengue hemorrhagic fever, or shock syndrome without atypical manifestations. Atypical manifestations were found in 30 patients (48.38%) of our study. Eleven (17.7%) patients had splenomegaly, 5 (8.1%) patients had hepatitis, 3 (4.8%) patients had diarrhea, 2 (3.2%) patients had acalculous cholecystitis, 1 (1.6%) patient had hepatitis with acalculous cholecystitis, 1 (1.6%) patient had hepatitis with diarrhea, 1 (1.6%) patient had myocarditis, 1 (1.6%) patient had paroxysmal supraventricular tachycardia, 1 (1.6%) patient had acute pancreatitis, 1 (1.6%) patient had acute kidney injury, 1 (1.6%) patient had ARDS, 1 (1.6%) patient had encephalitis, and 1 (1.6%) patient had myositis. Need of intensive care facility was more in patients with atypical manifestations due to mis or late diagnosis which prolonged course of stay. Conclusion: Atypical manifestations of DF are more common than reported. Lack of awareness among physicians, especially in primary health center, leads to delayed diagnosis and increased mortality and morbidity.